2017
DOI: 10.1073/pnas.1620739114
|View full text |Cite
|
Sign up to set email alerts
|

Older, sociable capuchins (Cebus capucinus) invent more social behaviors, but younger monkeys innovate more in other contexts

Abstract: An important extension to our understanding of evolutionary processes has been the discovery of the roles that individual and social learning play in creating recurring phenotypes on which selection can act. Cultural change occurs chiefly through invention of new behavioral variants combined with social transmission of the novel behaviors to new practitioners. Therefore, understanding what makes some individuals more likely to innovate and/or transmit new behaviors is critical for creating realistic models of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 48 publications
3
63
0
2
Order By: Relevance
“…Cultural transmission also has large-scale evolutionary implications for some nonhuman animals: For example, theoretical studies suggest that nonrandom mating in birds based on culturally transmitted songs could accelerate speciation (180,181) and that sexual selection on learned songs could influence evolution of the neural underpinnings of learning (182). Recently, studies in a range of animal species have shown that cultural practices can emerge, spread, and change over time, potentially influencing individuals' fitness (183)(184)(185)(186)(187). Tool use among chimpanzees and capuchins (188)(189)(190)) is one such example, which also provides insight regarding the possible origins of the early phases of our own species' adaptation to the "cultural niche" (191,192).…”
Section: Discussionmentioning
confidence: 99%
“…Cultural transmission also has large-scale evolutionary implications for some nonhuman animals: For example, theoretical studies suggest that nonrandom mating in birds based on culturally transmitted songs could accelerate speciation (180,181) and that sexual selection on learned songs could influence evolution of the neural underpinnings of learning (182). Recently, studies in a range of animal species have shown that cultural practices can emerge, spread, and change over time, potentially influencing individuals' fitness (183)(184)(185)(186)(187). Tool use among chimpanzees and capuchins (188)(189)(190)) is one such example, which also provides insight regarding the possible origins of the early phases of our own species' adaptation to the "cultural niche" (191,192).…”
Section: Discussionmentioning
confidence: 99%
“…However, innovations that are effortful and rare when they first appear within a generation can become effortlessly and widely adopted by the next generation. In fact, among nonhuman animals, cultural innovations are often first produced, adopted, and spread by juveniles (55)(56)(57)(58).…”
mentioning
confidence: 99%
“…Di Bitetti (1997) verificou que os pares de indivíduos que realizam catação com maior frequência são os mesmos que formam alianças mais fortes. Alguns estudos realizados com Cebus capucinus relataram que as fêmeas dominantes recebem a maior parte das catações (Perry et al, 2017, Rose, 1998 catações com maior frequência nas fêmeas subordinadas do que o inverso (Parr et al, 1997).…”
Section: Vida Socialunclassified